Genotype x environment interaction and stability analysis of seed yield in navy bean genotypes - Gebeyehu, S; Assefa, H. (2003)
Genotype x environment interactions, genotype response to environments and stability for seed yield of navy bean genotypes (Phaseolus vulgaris L.) were studied. Sixteen genotypes were grown in a randomised complete block design with three replications at four locations in Ethiopia. Genotype x environment (G X E) interactions were analysed using linear regression. There was considerable variation in seed yield within and across environments. Genotype x environment interaction was present, the highest being the linear component. The significance of the linear proportion demonstrated the adequacy of the regression model in describing the stability of the bean genotypes. Two genotypes, G 17450 and PAN 134 with respective regression coefficient values of 1.04 and 1.09, smaller S2d values, and a relatively high seed yield could be considered the most widely adapted genotypes. The other test genotypes were sensitive to production-limiting factors, their wider adaptability, stability and general performance to the fluctuating growing conditions within and across sites being lowered.